Investigating Integration: The Geographies of the WUSC Student Refugee Program at the University of British Columbia - Plasterer, Robyn (Refuge: Canada’s Journal on Refugees, 2011)
This paper examines the geographies of resettlement and integration with respect to the Student Refugee Program(SRP) of the World University Service of Canada (WUSC).As Canada’s only program to link resettlement with post-secondary education, the SRP makes manifest intriguing geographies that intersect international, national, and local scales. Th is study carried out the first qualitative research of the WUSC SRP at the University of British Columbia (UBC). It draws from good settlement practices,refugees’ existing skill sets, and refugees’ perspectives to examine how refugee students’ human capital can best contribute to Canadian integration.